Kestabilan Inokulan Azotobacter selama Penyimpanan pada Dua Suhu - Hindersah, Reginawanti; Sudirja, Rija (Jurnal Natur Indonesia, 2011)
Azotobacter might be used as biological agents in bioremediation of heavy metal-contaminated soil since this rhizobacteria produceexopolysachharides (EPS) that mobilize soil heavy metals, and phytohormones that regulate root growth. So that heavy metal uptake bythe roots could be increased. The objective of this research was to verify the stability of EPS and phytohormones in Azotobacter liquidinoculants during four months in different temperature storage. Liquid inoculants has been produced in EPS-induced media and stored in200C and room temperature (24-270C) during four months. The results showed that the better temperature storage was room temperatureinstead of 20 0C since pH, total N, and EPS and phytohormones content was relatively stable during storage.